Correlation and Path Analysis in Barley under Rainfall Conditions - Tawfiq, Sherwan I.; Abdulkhaleq, Dana Dana A.; Hama, Shara J.; Qbdulaqder, Shang H. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Some genotypes of six-rowed barley (Hordeumvulgare L.) were cultivated under rainfall conditions at two winter growing seasons 2012-2013 and 2013-2014 in the fields of Agriculture Research Station at Qlyasan, Faculty of Agricultural Sciences, University of Sulaimani in order to study the relationships between some agronomic traits and to identify the most important traits of a direct effect of the grain yield to be adopted as a criterion for selection. Highly significant and positive correlation were present between grain yield and all characters at both seasons except straw yield which was not significant at the first season and it was significant and positive at the second season, and harvest index at the first season which was significant and positive.Maximum positive direct effect in grain yield recorded by biological yield at both seasons, while maximum indirect effect recorded by 1000-grain weight via biological yield at the first season and straw yield via biological yield at the second season.
Keywords: Genotypes; Grain yield; Correlation coefficient and path analysis